Dietary intervention with narrow-leaved cattail rhizome flour (Typha angustifolia L.) prevents intestinal inflammation in the trinitrobenzenesulphonic acid model of rat colitis - Fruet Andréa; Seito Leonardo; Rall Vera Lúcia; Di Stasi Luiz (BMC, 2012)
Abstract Background Inflammatory bowel disease (IBD) is a chronic inflammation of the intestinal epithelium that is driven by the intestinal immune system, oxidative stress and the loss of tolerance to the luminal microbiota. The use of dietary products containing ingredients such as fibres and carbohydrates and/or antioxidant compounds have been used as a therapeutic strategy for intestinal diseases because these products are considered effective in the modulation of the immune system and colonic microbiota. We investigated the beneficial effects of cattail rhizome flour (Typha angustifolia L.) in the trinitrobenzenesulphonic acid (TNBS) model of rat colitis. In addition, we investigated the effects of cattail rhizome flour on the intestinal anti-inflammatory activity of prednisolone, which is a reference drug that is used for treatment of human IBD. Methods The present study included the preparation of flour from rhizomes of cattail (Typha angustifolia L.); an evaluation of the qualitative phytochemical profile of cattail rhizomes; an evaluation of the efficacy of cattail rhizome flour in TNBS-induced rat colitis; an evaluation of the synergistic effects of cattail rhizome flour on the intestinal anti-inflammatory activity of prednisolone; and macroscopic, clinical, biochemical, histopathological and microbiological studies to assess the healing effects of cattail rhizome flour and its synergistic effects in TNBS-induced rat colitis. The data were analysed by ANOVA, Kruskal-Wallis and χ2 tests. Results We tested several concentrations of cattail rhizome flour and found that dietary supplementation with 10% cattail rhizome flour showed the best effects at reducing the extension of the lesion, the colon weight ratio, adherences to adjacent organs and diarrhoea. These effects were related to inhibition of myeloperoxidase (MPO) and alkaline phosphatase (AP) activities and an attenuation of glutathione (GSH) depletion. The 10% cattail rhizome flour was as effective as prednisolone, and no synergistic effects were observed. Saponins, flavonoids and coumarins were detected in the rhizome flour. No changes were observed in the total number of lactic bacteria after dietary supplementation with cattail rhizome flour. Conclusions Dietary supplementation with 10% cattail rhizome flour and its combination with prednisolone prevent TNBS-induced colonic damage in rats, but no synergistic effects were observed. The prevention of TNBS-induced colon damage was associated with an improvement in intestinal oxidative stress, which likely resulted from the antioxidant properties of the active compounds detected in the cattail rhizome. This protective effect was not related to an improvement in lactic bacteria counts.